Impact of network physical topology on planning multiband optical networks aware of physical layer impairments - Vaz, M. (2023)
A multiband planning tool is developed in this work to solve the routing, modulation format and spectrum as signment problem and is used to discuss the influence of the network physical topology on several parameters considering four optical network topologies, different target bit error rates (BERs) and transmission capacities. We conclude that, in non-regenerated optical links, the length of the network links has a direct impact on the percentage of blocked demands leading to a higher assignment of lower modulation formats. This effect is particularly pronounced when considering lower BERs, higher information bit rates and full mesh logical topologies.